Disasters and Elections: Estimating the Net Effect of Damage and Relief in Historical Perspective. (3rd April 2017) - Heersink, Boris; Peterson, Brenton D.; Jenkins, Jeffery A.
Abstract : Do natural disasters help or hurt politicians' electoral fortunes? Research on this question has produced conflicting results. Achen and Bartels (2002, 2016 ) find that voters punish incumbent politicians indiscriminately after such disasters. Other studies find that voters incorporate the quality of relief efforts by elected officials. We argue that results in this literature may be driven, in part, by a focus on contemporary cases of disaster and relief. In contrast, we study a case of catastrophic flooding in the American South in 1927, in which disaster aid was broadly and fairly distributed and Herbert Hoover (the 1928 Republican presidential candidate) was personally responsible for overseeing the relief efforts. Despite the distribution of unprecedented levels of disaster aid, we find that voters punished Hoover at the polls: in affected counties, Hoover's vote share decreased by more than 10 percentage points. Our results are robust to the use of synthetic control methods and suggest that—even if voters distinguish between low- and high-quality responses—the aggregate effect of this disaster remains broadly negative. Our findings provide some support for Achen and Bartels' idea of blind retrospection, but also generate questions about the precise mechanisms by which damage and relief affect vote choice.